Peran Hukum Islam dalam Pembangunan Hukum Nasional di Indonesia - Husaini, Hasan; Mariani, Mariani; Hasan, Ahmadi; Jalaluddin, Jalaluddin (Universitas Ekasakti, 2023)
The development of national law in Indonesia is a complex process involving various issues, interests, and expectations. Islamic law plays a crucial role in shaping the national legal system as one of the acknowledged sources of law. However, challenges in integrating Islamic law with national law encompass the diversity of interpretations, harmonization with constitutional principles, and practical obstacles in implementation. This study employs a literature review method with a normative approach. The literature review method is utilized to explore and analyze various documents and literature concerning the integration of Islamic law into the national legal system, enabling a more profound understanding of Islamic law and national law. The study's conclusion underscores the significant role of Islamic law in the development and formation of national law in Indonesia. Islamic law strongly influences the shaping of legal norms and values within the national legal system. Nevertheless, the integration of Islamic Law with National Law faces challenges and obstacles that must be overcome, including diverse interpretations, consensus among various parties, and a deep understanding of Islamic law within Indonesia's social context.